Phase change material for the thermal protection of ice cream during storage and transportation. (April 2015) - Leducq, D.; NDoye, F.T.; Alvarez, G.
Abstract: Ice cream is a very temperature sensitive product and temperature variations during the storage and distribution steps may result in a reduction of quality. It is possible to improve the ice cream storage and transportation conditions by using an additional packaging with a low thermal diffusivity. This paper studies a phase change material (PCM) packaging and compares its performance to a polystyrene packaging configuration. The impact on temperature fluctuations and ice crystal size distribution was characterized experimentally during long term storage and temperature abuse. The results show that the use of an additional PCM packaging has a significant impact on the final quality of the product by keeping ice cream temperature stable and close to the phase change temperature of the PCM material. These results were compared with the insulation material results and discussed, showing that a material with a buffering heat capacity can be more efficient to reduce temperature fluctuations than a low conductivity material, and that the same results can be usually obtained with a much thinner layer of material. Highlights: We compare a PCM packaging with a polystyrene packaging for ice cream. The effect on a long term storage with temperature fluctuations is evaluated. We show that an additional PCM packaging has a significant impact on product quality. PCM packaging is more efficient to reduce temperature fluctuations than insulation. Rise of temperature in case of temperature abuse is more limited with PCM packaging.